Elite response to protest in authoritarian settings: evidence from Russia. Issue 6 (18th August 2021) - Bryan, James D.; Perevezentseva, Anastassiya
ABSTRACT: Scholars of contentious politics understand the critical role of opposition protests and the elite in influencing regime outcomes. What is less understood, however, is how opposition protest can impact the "hearts and minds" of elites in authoritarian settings. Using the timing of the Survey of Russian Elites and a 2016 protest in Moscow to commemorate the death of a Russian opposition figure, we show that elites initially responded with sympathy to the peaceful and well-attended protest, but those feelings faded in the weeks following the event. We attribute the ephemeral nature of the protest's impact to a successful strategy by the Kremlin to acknowledge the event and then promptly ignore it in the following weeks. We posit this allowed the event to leave the consciousness of most elites and their feelings returned to pre-protest levels. Our findings suggest that certain opposition protests can garner sympathy among the elite in authoritarian settings, but also highlight the passive tools of authoritarian regimes in minimizing the impact of protest movements. Opposition movements, thus, not only have to cue sympathetic feelings among the elite, but also have to sustain that persuasion in subsequent news cycles.